2020
DOI: 10.1038/s41467-020-19246-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunizing lithium metal anodes against dendrite growth using protein molecules to achieve high energy batteries

Abstract: The practical applications of lithium metal anodes in high-energy-density lithium metal batteries have been hindered by their formation and growth of lithium dendrites. Herein, we discover that certain protein could efficiently prevent and eliminate the growth of wispy lithium dendrites, leading to long cycle life and high Coulombic efficiency of lithium metal anodes. We contend that the protein molecules function as a “self-defense” agent, mitigating the formation of lithium embryos, thus mimicking natural, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 42 publications
5
141
0
Order By: Relevance
“…In addition, the XPS results indicated that the STCA coating reduced the formation of unstable SEI components (Li 2 O and Li 2 CO 3 ). [ 64,65 ] Moreover, at different etching times, they were consistent with the cryo‐TEM visualization, that is, the LiF was concentrated in the SEI nanostructure. Therefore, the STCA coating was reconfirmed to yield a stable LiF‐enriched SEI, eliminating the Li dendrites.…”
Section: Resultssupporting
confidence: 73%
“…In addition, the XPS results indicated that the STCA coating reduced the formation of unstable SEI components (Li 2 O and Li 2 CO 3 ). [ 64,65 ] Moreover, at different etching times, they were consistent with the cryo‐TEM visualization, that is, the LiF was concentrated in the SEI nanostructure. Therefore, the STCA coating was reconfirmed to yield a stable LiF‐enriched SEI, eliminating the Li dendrites.…”
Section: Resultssupporting
confidence: 73%
“…strong polar solvent and changeable electric field), these complexes bonded by loose forces would promote the sustained release effect with inorganic POM escaping from the bondage of organic cations or molecules.Asaresult, POM clusters encapsulated in organic shells just behave like aslow-released additive as the cases of LiF placed in porous Al 2 O 3 ceramics,L iNO 3 anchored in PVDF-HFP matrix, montmorillonite suspended in PEO, NaMg(Mn)F 3 wrapped in C, and fibroin molecule chained to electrospinning interlayer. [7,[61][62][63][64] Although the starting point for designing as low-released additive is to solve its dissolution problem in the target electrolyte,t he slow consumption and continuous functionalization effectively guarantee ah ighly stable anode during repeated cycling (Table S5). Benefiting from the shell adsorption effect of these additives,e xtra anions (TFSI À ,N O 3 À )w ould be attracted to the anode side and contribute to the formation of SEI layer rich in LiF and Li x NO y (Figure 2e and f).…”
Section: Methodsmentioning
confidence: 99%
“…In October 2020, for example, Cui's group at Stanford described how to implement a kind of "self-defense" system in a lithium-metal battery by adding a protein called fibroin to the electrolyte. Those proteins, they observed, attached not only to the surface of the lithium metal anode but also to the "buds" of newly formed dendrites (7). When a dendrite was completely covered by fibroin, incoming lithium ions didn't attach to the end and instead formed neat layers rather than clumpy three-dimensional protuberances.…”
Section: How To Block a Dendritementioning
confidence: 99%